Perlindungan Hukum Bagi Pasien Akibat Diberlakukannya Surat Edaran Kemenkes Tentang Himbauan Tidak Praktik Kecuali Emergensi - Alde Erfajrin Syabana (Faculty of Law, Universitas Airlangga, 2022)
AbstractAs a rule of law, it is appropriate for the Indonesian government to fulfill the rights that guaranteed and regulated through statutory regulations. However, in practice, it is not uncommon for the Indonesian government to issue policies that are deemed to violate the rights of its citizens. One example is the issuance of a Form Letter of the Ministry of Health Number YR.03.03 / III / III8 / 2020 concerning Appeals for No Practices except Emergencies by the Director General of Health Services. The form letter is deemed to have violated the rights of citizens, especially in health services. In order to guarantee the rights of citizens, it is necessary to have legal protection. This legal protection is a step for citizens who feel aggrieved by the issuance of this form letter. This paper aims to find out what efforts can be made by citizens if they feel aggrieved by this form letter as a measure of legal protection. This paper uses the Reform-oriented Research method with a statutory approach and a conceptual approach.Keywords: Rights; Legal Protection; From Letter. AbstrakSebagai negara hukum, sudah sepantasnya bagi pemerintah Indonesia untuk memenuhi hak-hak yang dijamin dan diatur melalui peraturan perundang-undangan. Namun dalam praktiknya, tak jarang pemerintah Indonesia menerbitkan kebijakan-kebijakan yang dirasa melanggar hak-hak warga negaranya. Salah satu contohnya adalah dengan diterbitkannya Surat Edaran Kementerian Kesehatan Nomor YR.03.03/III/III8/2020 Tentang Himbauan Tidak Praktik Kecuali Emergensi oleh Dirjen Pelayanan Kesehatan. Surat edaran tersebut dianggap melanggar hak warga negara khususnya dalam pelayanan kesehatan. Dalam rangka menjamin hak-hak warga negaranya, maka perlu adanya perlindungan hukum. Perlindungan hukum ini menjadi langkah bagi warga negara yang merasa dirugikan akibat diterbitkannya surat edaran tersebut. Tulisan ini bertujuan untuk mengetahui upaya apa yang dapat dilakukan oleh warga negara apabila merasa dirugikan oleh surat edaran tersebut sebagai langkah perlindungan hukum. Tulisan ini menggunakan metode Reform-oriented Research dengan pendekatan perundang-undangan dan pendekatan konsep. Kata Kunci: Hak-Hak; Perlindungan Hukum; Surat Edaran.